MuSK-antibodies are associated with worse outcome in myasthenic crisis requiring mechanical ventilation - Konig, Nicole; Stetefeld, Henning R.; Dohmen, Christian; Mergenthaler, Philipp; Kohler, Siegfried; Schonenberger, Silvia; Bosel, Julian; Lee, De-Hyung; Gerner, Stefan; Huttner, Hagen; Schneider, Hauke; Reichmann, Heinz; et al. (Journal of Neurology, 2021)
Myasthenic crisis (MC) is a life-threatening condition for patients with myasthenia gravis (MG). Muscle-specific kinase-antibodies (MuSK-ABs) are detected in 6% of MG, but data on outcome of MuSK-MCs are still lacking. We made a subgroup analysis of patients who presented with MC with either acetylcholine-receptor-antibody positive MG (AchR-MG) or MuSK-MG between 2006 and 2015 in a retrospective German multicenter study. We identified 19 MuSK-AB associated MCs in 15 patients and 161 MCs in 144 patients with AchR-ABs only. In contrast to patients with AchR-AB, MuSK-AB patients were more often female (p = 0.05, OR = 2.74) and classified as Myasthenia Gravis Foundation of America-class IV before crisis (p = 0.04, OR = 3.25). MuSK-AB patients suffer more often from multiple chronic disease (p = 0.016, OR = 4.87) and were treated more invasively in terms of plasma exchanging therapies (not significant). The number of days of mechanical ventilation (MV) (43.0 ± 53.1 vs. 17.4 ± 18; p < 0.0001), days on an intensive care unit (ICU) (45.3 ± 49.5 vs. 21.2 ± 19.7; p < 0.0001), and hospital-length of stay (LOS) (55.9 ± 47.6 vs. 28.8 ± 20.9 days; p < 0.0001) were significantly increased in MuSK-MC. Remarkable is that these changes were mainly due to patients with MusK-ABs only, whereas patients’ outcome with both antibodies was similar to AchR-MCs. Furthermore, our data showed a shortened duration of MV after treatment with plasma exchanging therapies compared to treatment with intravenous immunoglobulin in MuSK-MCs. We conclude that MuSK-AB-status is associated with a longer need of MV, ICU-LOS, and hospital-LOS in MC, and therefore recommend early initiation of a disease-specific therapy.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Antibody status; Autoimmune diseases; MuSK-antibodies; Myasthenia gravis; Myasthenic crisis; Outcome